Building a network concept in contemporary public administration - Husna, Khuriyatul; Kusumasari, Bevaola; Pramusinto, Agus (2019)
This study aims to provide an overview of the literature on network research that developed in public administration studies over a period of ten years (2007–2016). Besides this, it also observes whether a consensus on the network concept was reached among scholars during this time period. The differences in approaches and perspectives used by public administration scholars in understanding networks each have their own implications on the heterogeneity of network research. Such differences, hence, influence the way they define networks. The rise in the amount of research and differences in the use of the “term” network indicates that clarity in the network concept has yet to be reached. The contribution of this study is based on the fact that the field of public administration needs to be more aware of the network literature in other disciplines and to employ this research to advance the understanding of network issues in the public sector context. © 2019 National Research University Higher School of Economics. All rights reserved.